1995
DOI: 10.1152/jappl.1995.79.6.1878
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen tension in the bladder epithelium rises in both high and low cardiac output endotoxemic sepsis

Abstract: The effect of endotoxin on tissue oxygen tension measured at the bladder epithelium was assessed in spontaneously breathing Sprague-Dawley rats anesthetized with halothane. Hyperdynamic (high cardiac output, group A, n = 6) and hypodynamic (low cardiac output, group B, n = 6) circulatory responses were achieved by intravenous administration of Escherichia coli lipopolysaccharide, 10 mg/kg over 30 min or 20 mg/kg over 1 min, respectively. Comparison was made against sham-operated control rats (group C, n = 6). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 0 publications
5
40
0
1
Order By: Relevance
“…Although mitochondrial dysfunction and sustained local oxygenation have been described in tissues obtained from experimentally septic mammals (heart, skeletal muscle, and liver) and human subjects with sepsis (skeletal muscle biopsies) (29)(30)(31)(32)(33)(34), less work has been done to test this hypothesis in sepsis-associated AKI. Prior studies have shown that in the first 1-4 hours after intravenous endotoxin exposure, intrarenal oxygen consumption is unchanged despite reduced delivery (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Although mitochondrial dysfunction and sustained local oxygenation have been described in tissues obtained from experimentally septic mammals (heart, skeletal muscle, and liver) and human subjects with sepsis (skeletal muscle biopsies) (29)(30)(31)(32)(33)(34), less work has been done to test this hypothesis in sepsis-associated AKI. Prior studies have shown that in the first 1-4 hours after intravenous endotoxin exposure, intrarenal oxygen consumption is unchanged despite reduced delivery (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…During endotoxinemia and sepsis, glycolytic ATP production was increased (5). Apparently, OxPhos was inhibited, although increased tissue oxygen levels suggest cellular availability of O 2 (6), indicating a decrease of oxygen utilization (7,8).…”
mentioning
confidence: 99%
“…Direct and indirect evidence exists for the development of cytopathic hypoxia in sepsis (or related inflammatory conditions, such as endotoxemia) in experimental animals. For example, tissue PO 2 has been shown to increase in rats (33) and pigs (42) infused with purified lipopolysaccharide (LPS) and also in human patients with septic shock (5). In an indirect way, these data suggest that the ability of cells to extract O 2 from arterial blood is impaired in these conditions, which are associated with systemic inflammation.…”
mentioning
confidence: 99%